(untitled) (Research, Society and Development, 2022)
Canine leproid granuloma is a nodular dermatosis that can affect cutaneous and subcutaneous regions, usually located in ears and extremities. It is known that the immunity of dogs is an important ally both to combat their development, as well as for spontaneous regression in affected animals without surgical excision or use of antibacterials. Due to that, this study aims to report a case of leproid granuloma in a dog, diagnosed by cytopathology, emphasizing its appearance secondary to immunosuppression resulting from previous chemotherapy treatment. The canine, male, mixed breed, 9 years old and weighing 29.4kg was seen at the Veterinary Hospital of the University of Passo Fundo, in Rio Grande do Sul, with a complaint of an ulcerated and bloody lesion on the penis. Fine-needle cytology was performed and a transmissible venereal tumor was diagnosed. After the sixth chemotherapy session with vincristine sulfate, he presented a nodule on the external surface of the left ear measuring 1.5x1.2cm, firm consistency, and regular appearance, non-inflamed and adherent. Cytopathology and special staining with Ziehl-Neelsen were performed, confirming that it was a granulomatous inflammation resulting from an infection caused by Mycobacterium spp. We emphasize that the patient’’s immune response is an important variable to be considered in the appearance of canine leproid granuloma. And thus, this differential diagnosis should always be considered in patients who start to present nodular skin changes after stipulating chemotherapy protocols.